P Peran Mahasiswa KKN dalam Penanggulangan Banjir dan Pemberdayaan Masyarakat di Desa Lok Buntar: The Role of KKN Students in Flood Management and Community Empowerment in Lok Buntar Village - Mafulloh, M. Roy; Hasnah, Hasnah; Maulida, Ehda; Nisa, Norhikmatun; Safitri, Aulia; Jum'ah, Jum’ah; Cahyati, Cahyati; Santoso, Akhmad; Pribakti, Subhan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2025)
Lok Buntar Village in Sungai Tabuk District frequently encounters seasonal flood threats that result in infrastructural damage and heighten residents' economic and psychosocial vulnerabilities. This community service aims to optimize the role of Student Community Service (KKN) participants through a holistic approach that synergizes disaster management with community empowerment. The implementation employs the Participatory Action Research (PAR) method, involving active collaboration between ten students and the community through stages of needs diagnosis, integrated action implementation, participatory observation as field coordinators, and impact reflection. Results indicate significant achievements across various sectors: (1) logistics management via the accountable distribution of 150 aid packages and communal kitchen operations; (2) psychosocial support through anti-bullying socialization for 35 elementary school students; (3) enhanced environmental education through the installation of three waste education signs; and (4) governance improvement through the redesign of the village organizational structure. This service concludes that integrating physical and non-physical programs within KKN activities transforms students into effective agents of change in building community resilience. The established cross-sector synergy provides tactical solutions to flood impacts while strengthening the administrative and social capacity of Lok Buntar Village in a sustainable manner.